Grounding Zone of Amery Ice Shelf, Antarctica, From Differential Synthetic‐Aperture Radar Interferometry - Chen, Hanning; Rignot, Eric; Scheuchl, Bernd; Ehrenfeucht, Shivani (Geophysical research letters, 2023)
We employ a time series of Sentinel‐1 differential radar interferometry data from 2018 to detect the variability in grounding line position of the Fisher, Mellor, and Lambert glaciers, which drain about 47 billion tons of ice per year from East Antarctica. We observe kilometer‐scale tidal migration, two orders of magnitude larger than expected for ice flowing over a hard bed. The migration is not in phase with changes in oceanic tide. In two estuaries underlaid by subglacial channels, we observe two states of migration that switch on and off over time scales of several weeks. The range of vertical motion reveals a water column thickness of 2–20 cm. Such intrusions of seawater over wide grounding zones are not accounted for in physical models. Including them will add vigorous melting of grounded ice that will enhance the sensitivity of glaciers to ocean warming and increase projections of mass loss. Plain Language Summary Grounding lines (GLs) are assumed to migrate back and forth with changes in oceanic tides based on hydrostatic equilibrium, which induces horizontal migration in the range of a few 100 m, similar to the spatial resolution of ice sheet models. Differential radar interferometry data from the Sentinel‐1 mission, however, reveals that for the Fisher, Mellor, and Lambert glaciers, the migration is two orders of magnitude larger. Such widespread intrusions of seawater will melt grounded ice and affect the regime of basal friction of glaciers and their stability. Physical models in charge of projecting sea level rise assume a fixed GL, with zero melt. We report regions of enhanced migration (10–15 km) along estuaries underlaid by subglacial channels where water gets trapped for several weeks before draining out. These irregular, widespread interactions between ice and seawater will have a strong impact on glacier evolution and projections if implemented in physical models. Key Points The zone of tidal variability of Amery Ice Shelf grounding line (GL) is two orders of magnitude wider than expected from hydrostatic equilibrium We detect GL migration uncorrelated with tide up to 15 km upstream, along subglacial troughs, with 2–20 cm thick water intrusions Seawater intrusion in estuaries has high potential for melting ice in grounding zone and enhance sensitivity of glaciers to ocean warming